The Solvability and Optimal Controls for Some Fractional Impulsive Equation. (21st October 2013) - Liu, Xianghu; Liu, Zhenhai; Han, Jiangfeng
Abstract : This paper is concerned with the existence and uniqueness of mild solution of some fractional impulsive equations. Firstly, we introduce the fractional calculus, Gronwall inequality, and Leray-Schauder's fixed point theorem. Secondly with the help of them, the sufficient condition for the existence and uniqueness of solutions is presented. Finally we give an example to illustrate our main results.